The Influence of Brand and Country of Origin on Mobile Phone Purchasing Decisions - Hasan, Adnan (Advances in Business & Industrial Marketing Research, 2023)
The background of this research is the increasing number of mobile phone brands circulating with different specifications and originating from other countries; public perceptions regarding brands and country of origin also influence a person's purchase of something, including the purchase of a mobile phone. In making mobile phone purchasing decisions, one is controlled by the brand and the country of origin. This study aimed to determine the effect of brand and country of origin on consumer attitudes toward choosing mobile phones for Institut Agama Islam Negeri Parepare students. The sample that became the object of research was 100 students. The analytical method used in this study is multiple linear regression with the help of the SPSS 23 application. This study's results indicate a significant influence between brands and country of origin on consumer attitudes toward choosing mobile phones for Institut Agama Islam Negeri Parepare students. The country-of-origin variable is the most important factor influencing consumer attitudes in selecting mobile phones.